Ho Rih Hua Lecture: Senior Minister Lee Kuan Yew (Institutional Knowledge at Singapore Management University, 2002)
Audience at an address by Singapore’s Senior Minister Lee Kuan Yew. He gave the inaugural address, entitled An Entrepreneurial Culture for Singapore, at Singapore Management University's Ho Rih Hwa Leadership in Asia Public Lecture Series. The lecture series presents the views of entrepreneurs, business and political leaders from within and beyond the Asia-Pacific region. Photo taken at Suntec City Convention Centre on 5 February 2002.